STUDI POPULASI SEMUT RANGRANG Oecophylla smaragdina (HYMENOPTERA: FORMICIDAE) DI DESA SIRILOGUI KECAMATAN SIBERUT UTARA KABUPATEN KEPULAUAN MENTAWAI - -, Ertha - (STKIP PGRI Sumbar, 2014)
Rangrang Ant Oecophylla smaragdina is an insect which is often found in tree like frurt similan to lychee, manggo, cacao, clove, rose apple, mangosteen, etc. Rangrang ant can hunt pest like green dented, caterpillar which eat leaf and other insect fruit pest. Related to it, it has been done research about population of rangrang ant Oecophylla smaragdina (Hymenoptera : Formicidae) in Sirilogui village Nonth Siberut Mentawai Island District in August 2013 with the purpose to know the population of rangrang ant which is talking about nest population and nest characteristic of rangrang ant. The research used descriptive survey method by observing rangrang ant nest directly which can be found in research location. The parameter which used are stem diameter, branch, small branch, height of nest, and plant types name of nest. For the research result which has been done, it can be gotten that rangrang ant nest which were located in cacao plantation and the lowest in scrub. The plant as the nests like Eugenia aromatica, Theobroma cacao, Macaranga tanarius, Glochidion sp, Dendrolobium umbellatum, Vitex pubescens, Leea indica.The stem diameter which is mostly found in about 5-10cm in 10 nests, the most nest which is found in branch is 1-3 is 36 nest and small branch 6-10 is 22 nests. The high nest mostly found in 1-2 meter from land surface. Itâs 26 nests.